Successful matched sibling donor marrow transplantation following reduced intensity conditioning in children with hemoglobinopathies. Issue 12 (6th October 2015) - King, Allison A.; Kamani, Naynesh; Bunin, Nancy; Sahdev, Indira; Brochstein, Joel; Hayashi, Robert J.; Grimley, Michael; Abraham, Allistair; Dioguardi, Jacqueline; Wah Chan, Ka; Douglas, Dorothea; Adams, Roberta; et al.
Abstract : Fifty‐two children with symptomatic sickle cell disease sickle cell disease (SCD) (N = 43) or transfusion‐dependent thalassemia (N = 9) received matched sibling donor marrow (46), marrow and cord product (5), or cord blood (1) allografts following reduced intensity conditioning (RIC) with alemtuzumab, fludarabine, and melphalan between March 2003 and May 2014*. The Kaplan–Meier probabilities of overall and event‐free survival at a median of 3.42 (range, 0.75–11.83) years were 94.2% and 92.3% for the group, 93% and 90.7% for SCD, and 100% and 100% for thalassemia, respectively. Treatment‐related mortality (all related to graft versus host disease, GVHD) was noted in three (5.7%) recipients, all 17–18 years of age. Acute and chronic GVHD was noted in 23% and 13%, respectively, with 81% of recipients off immunosuppression by 1 year. Graft rejection was limited to the single umbilical cord blood recipient who had prompt autologous hematopoietic recovery. Fourteen (27%) had mixed chimerism at 1 year and beyond; all had discontinued immunosuppression between 4 and 12 months from transplant with no subsequent consequence on GVHD or rejection. Infectious complications included predominantly bacteremia (48% were staphylococcus) and CMV reactivation (43%) necessitating preemptive therapy. Lymphocyte recovery beyond 6 months was associated with subsidence of infectious complications. All patients who engrafted were transfusion independent; no strokes or pulmonary complications of SCD were noted, and pain symptoms subsided within 6 months posttransplant. These findings support using RIC for patients with hemoglobinopathy undergoing matched sibling marrow transplantation (*www.Clinical Trials.gov : NCT00920972, NCT01050855, NCT02435901). Am. J. Hematol. 90:1093–1098, 2015. © 2015 Wiley Periodicals, Inc.